Shiga toxin Escherichia coli survival in different blending ratio of fresh pineapple-mango juice blends - Kamarul Zaman, Amanina Amani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Shiga toxin producing E. coli (STEC) of serotype O157:H7 widely known to cause hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS) which may lead to fatality. Mixed fruit juice were among the reported outbreak of E. coli O157:H7 as the pathogen able to adapt to acidic environment of fruit juice. Different blending ratio of pineapple and mango juice blend results with acidic range pH of 3.96±0.010 to 4.86±0.006 with blending ratio of 70% pineapple:30% mango; 50% pineapple:50% mango and 30% pineapple: 70% mango. The initial microbiological analysis on pineapple and mango juice blends however, results with no significant detection of STEC on all blending ratios as the colonies were too few to count. Inoculation of pineapple and mango juice blends with STEC of serotype O157:H7 shows blending ratio of 50% pineapple: 50% mango have highest STEC count (2.81 log cfu/ ml) and yeast and mould counts (YM) (8.65±0.64 log cfu/ml) compared to other ratios. Total plate count (TPC) however, shows deviate results as blending ratio of 70% pineapple: 30% mango results with highest TPC counts (8.29±0.25 log cfu/ ml).